HUBUNGAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK THRIFTING DI MEDIA SOSIAL INSTAGRAM - El Raihan , Zulham; Muslikhah , Febri Falupi; Nirwana , Testa Pradia (Fakultas Ilmu Dakwah dan Komunikasi, 2024)
The increasingly rapid development of technology and information, the concept of informal communication such as online discussions has developed until the term E-WOM (electronic word of mouth) emerged. Apart from that, E-WOM allows a consumer to determine whether to buy a product from a brand and find out the advantages or disadvantages. This product. The presence of thrifting makes it an alternative, especially for teenagers, to be able to get fashion according to their tastes. The quality offered by thrifting sellers is no less competitive than other new clothing. Therefore, the aim of this research was to determine the relationship between electronic word of mouth and the decision to purchase thrifting products on Instagram social media. This research uses quantitative methods. The sampling technique used was non-probability purposive sampling, the sample taken was 35 public respondents who had seen or bought thrifting products on Instagram. The data collection method used a questionnaire via Google Form. The results of the research show that there is a significant relationship between electronic word of mouth and the decision to purchase thrifting products on Instagram social media.